2001
DOI: 10.1016/s1010-7940(01)00695-9
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory dysfunction after coronary artery bypass grafting employing bilateral internal mammary arteries: the influence of intact pleura

Abstract: According to our results, we may conclude that pleural integrity has beneficial effects on the respiratory functional status after coronary revascularization using both IMAs. A meticulous and more careful IMA harvesting approach significantly reduces the postoperative morbidity regarding the pulmonary functional status, and as a consequence, reduces the hospital costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
52
1
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 19 publications
10
52
1
10
Order By: Relevance
“…All the IMAs in this study were harvested with a skeletonized technique, which has been demonstrated to better preserve sternal blood flow [23][24][25] and to reduce the risk of SWI. 26,27 Similarly, early reports of increased postoperative bleeding 28 and pulmonary morbidity 29 with BIMA grafting have not been substantiated by subsequent studies 30,31 and were not evident in the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…All the IMAs in this study were harvested with a skeletonized technique, which has been demonstrated to better preserve sternal blood flow [23][24][25] and to reduce the risk of SWI. 26,27 Similarly, early reports of increased postoperative bleeding 28 and pulmonary morbidity 29 with BIMA grafting have not been substantiated by subsequent studies 30,31 and were not evident in the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…Çalışmada ayrıca 21 hastaya plevral drenaj için ilave girişim (torasentez, göğüs tüpü yerleştirilmesi, reeksplorasyon) gerektiği ifade edilmiş-tir. Bonacchi ve ark., [9] plevra açılarak İMA çıkarılan hastalarda tek taraflı plevral efüzyon ve torasentez insidansının daha yüksek olduğunu bildirmişlerdir. Tulla ve ark.…”
Section: Discussionunclassified
“…Second, skeletonization improves blood supply to the sternum (measured by single photon emission computed tomography) [16] compared with pedicled harvesting. Third, skeletonization decreases the incidence of postoperative respiratory dysfunction because of less invasive harvesting (i.e., preserved pleural integrity in skeletonized ITA vs. pleurotomy in pedicled ITA) [17,18]. Lastly, skeletonization markedly reduces anterior chest pain and dysesthesia 3 months after surgery [19].…”
Section: Discussionmentioning
confidence: 99%